2005
DOI: 10.1177/0143034305060787
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of School Psychologists in Different Countries

Abstract: Teachers are probably the main group of professionals with whom school psychologists1 have most contact. Teachers are usually involved in making referrals of individual children, they may be expected to act on the advice of the school psychologist and they also work with school psychologists in consultation-based activities. It is therefore important to ascertain their views about the work of school psychologists in order for services to move forward in an evidenced informed manner. This article discusses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 17 publications
4
36
1
5
Order By: Relevance
“…These results are consistent with the dissatisfaction expressed by school psychologists concerning the large proportion of time designated to these tasks and consequent reduced time available for activities (Bradley-Johnson & Dean, 2000;Bramlett et al, 2002;Curtis et al, 2002;Farrell, Jimerson, Kalambouka, & Benoit, 2005;Levinson, 1990;Nastasi, 2004;Watkins, Crosby, & Pearson, 2001). No differences were found in relation to the number of systemic practices completed, or the importance of these practices, between systems, suggesting considerable consistency across systems.…”
Section: Discussionsupporting
confidence: 67%
“…These results are consistent with the dissatisfaction expressed by school psychologists concerning the large proportion of time designated to these tasks and consequent reduced time available for activities (Bradley-Johnson & Dean, 2000;Bramlett et al, 2002;Curtis et al, 2002;Farrell, Jimerson, Kalambouka, & Benoit, 2005;Levinson, 1990;Nastasi, 2004;Watkins, Crosby, & Pearson, 2001). No differences were found in relation to the number of systemic practices completed, or the importance of these practices, between systems, suggesting considerable consistency across systems.…”
Section: Discussionsupporting
confidence: 67%
“…First, there is some recent evidence suggesting that teachers in different countries would like EPs to spend less time on individual assessments and more on consultative and preventative work (Farrell et al, 2005) and this in itself could act as a lever to change. Second, in relation to EP practice in the USA, new legislation has been introduced stating that special educational assessments will no longer have to rely on IQ tests, and where placement decisions can be based multi disciplinary assessments and on data from a child's "Response to Intervention" which, according to Jimerson and Oakland (in press), has the potential to reduce the EPs' reliance on using IQ tests.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, over the past 20 years or so a number of surveys of teachers' perceptions of the EP role in the UK and USA indicate that, in the main, they expect them to carry out special education assessments (DfEE, 2000;Dowling & Leibowitz, 1994;Evans & Wright, 1987;Ford & Migles, 1979). Moreover, this finding is replicated in a survey of teachers' views of EPs in Estonia (Kikas, 1999), in a major survey of the views of 1,100 teachers in eight different countries (Farrell, Jimerson, Kalambouka, & Benoit, 2005) and in the chapters of a forthcoming international handbook on school psychology (Jimerson, Oakland, & Farrell, in press). In addition Gilman and Gabriel (2004) found that local education authority (LEA) administrators in the USA were even more committed than teachers to the view that the EPs' main role was to carry out assessments of children with special needs and to make recommendations for them to be placed in some form of segregated provision.…”
Section: Introductionmentioning
confidence: 94%
“…Um estudo realizado em 8 países, não envolvendo Portugal, sobre a percepção que os professores têm sobre o papel do psicólogo educacional, revelou que os professores esperam que o psicólogo desenvolva preferencialmente trabalho com os alunos com necessidades educativas especiais, identificando--os e sugerindo que continuem os seus estudos numa escola a que chamam especial (Farrel, Jimerson, Kalambouka, & Benoit, 2005 Na actualidade, comprovada a ineficácia de um sistema paralelo, naturalmente segregado de educação (Dyson & Millward, 1997;Farrel & Ainscow, 2002;Kluth, 2005) e, apesar dos testes psicométricos terem sido úteis para o rápido desenvolvimento da profissão (e.g., Reschly, 2000), dispomos de outros recursos que se tornam fundamentais envolver no processo de ensino-aprendizagem. Por exemplo, a própria escola, o diversificado grupo de alunos, as famílias e a comunidade envolvente, de forma a potenciar todos os agente educativos (Morgado, 2001).…”
Section: Psicologia Educacional E Educação Inclusivaunclassified